Penyuluhan Pembuatan Dodol Kolang-Kaling Di Teluk Betung Selatan - Syarif, Arman; Kholifah, Nurul; Gumay, Nanda Fathiyah (Jurnal Pemberdayaan Ekonomi, 2024)
Purpose: The author conducted this community service research with the aim of increasing the awareness and capability of the residents of Wonosari Village in managing household finances wisely, enabling them to allocate a portion of their income for savings despite challenging economic conditions. Methodology/approach: The Community Service Program conducted by Sekolah Tinggi Ilmu Ekonomi Ragam Tunas Lampung was implemented in two main stages. In the awareness stage, the community was educated on the importance of financial management and saving as a form of future investment. In the maturity stage, they were trained to manage household finances so that a portion of their income could be set aside for long-term savings. Results/findings: The community training program on kolang-kaling dodol production in Teluk Betung Selatan improved participants’ skills in processing local food ingredients into marketable products. It also enhanced financial awareness, encouraging participants to save part of their earnings. The activity fostered collective entrepreneurship and initiated the formation of a community-based microenterprise. Conclusion: The kolang-kaling dodol training improved community knowledge and skills in processing local products. Residents also began applying basic financial literacy, including setting aside income for savings. This activity encouraged the formation of collective micro-enterprises based on local potential. Limitations: This study was limited to one village and focused primarily on short-term behavioral change, without evaluating long-term sustainability or economic impact. Contribution: The program provides a practical model for integrating local food innovation with basic financial education to promote sustainable community-based entrepreneurship.